Clinical trials (Henry Stewart Talks, 2025)
Clinical trials introduction, Clinical trial purpose and structure, Phased clinical trial design, Randomization and blinding, Selecting trial endpoints, Ethical and participant protection, Oversight and monitoring, Data analysis and statistics, Regulatory submission and approval, Post-marketing and ongoing monitoring